Optimasi Produksi Virgin Coconut Oil dengan Metode Direct Micro Expelling [Production Optimization of Virgin Coconut Oil by Direct Micro Expelling Method] - Adhitya Yudha Pradhana; Ismail Maskromo; Nugroho Utomo; Engelbert Manaroinsong; Steivie Karouw; Rindengan Barlina (Buletin Palma, 2019)
Virgin Coconut Oil (VCO) production with dry extraction oils such as copra is time consuming and resulting in quality. The purpose of this study was to optimize the production of VCO using the Direct Micro Expelling-Flat Bed Dried (DME-FBD) method. This research was carried out at the Indonesian Palm Crops Research Institute (IPCRI) on January - March 2019 in the coconut processing unit of the postharvest laboratory using two coconut varieties, namely Mapanget Tall (MTT) and Salak Green Dwarf (SGD), each with 10, 11, and 12 months harvest period. The experimental design used a Completely Randomized Design (CRD) with 3 repetition. The results showed that the yield of VCO oil from coconut 11 months old of MTT was 18.39% (16 nuts/L VCO) with optimum DME-FBD temperature of approximately 40-88°C on plate and 36–72°C on grated coconut meat. VCO obtained from MTT coconut has a quality of 0.07% water content, free fatty acid 0,0017%, fresh aroma coconut, non-rancid with a value of 4.50, a distinctive of coconut oil taste of 4.10, and clear color of 4.30 accordingly with SNI 7381: 2008 and export quality requirements of APCC. Almost the same quality was obtained from SGD coconut with 11 months of harvest with a water content of 0.06%, free fatty acids 0.0018%, a fresh aroma of coconut with a value of 4.30, a distinctive of coconut oil taste of 4.00, and clear color 4.10.ABSTRAKProduksi Virgin Coconut Oil (VCO) dengan ekstraksi kering seperti kopra membutuhkan waktu lama dan metode yang digunakan kurang optimal. Tujuan penelitian adalah untuk melakukan optimasi produksi VCO dengan menggunakan metode Direct Micro Expelling-Flat Bed Dried (DME-FBD). Penelitian dilakukan pada bulan Januari-Maret 2019 di unit pengolahan kelapa laboratorium pascapanen, Balai Penelitian Tanaman Palma menggunakan dua varietas kelapa, yaitu kelapa Dalam Mapanget (DMT) dan kelapa Genjah Salak (GSK), masing-masing dengan umur panen 10, 11, dan 12 bulan. Rancangan percobaan menggunakan Rancangan Acak Lengkap (RAL) dengan 3 ulangan. Hasil penelitian menunjukkan rendemen minyak VCO tertinggi dari kelapa DMT umur 11 bulan, sebesar 18,39% (16 butir/L VCO) dengan suhu optimum sekitar 40-88°C di pelat dan 35-72°C pada kelapa parut, sedangkan rendemen VCO kelapa GSK umur 11 bulan sebesar 16,38%, tetapi dengan jumlah buah 26 butir untuk mendapatkan 1 liter VCO, dengan suhu optimum sekitar 42-94°C di pelat dan 36-72°C pada kelapa parut. VCO yang diperoleh dari kelapa DMT mempunyai kualitas kadar air 0,07%, asam lemak bebas 0,0017%, aroma khas kelapa segar, tidak tengik dengan nilai 4,50, rasa normal, khas minyak kelapa 4,10, dan warna jernih 4,30 yang sesuai dengan SNI 7381:2008 dan syarat mutu ekspor APCC. Kualitas yang hampir sama diperoleh dari kelapa GSK dengan umur panen 11 bulan dihasilkan kadar air 0,06%, asam lemak bebas 0,0018%, aroma segar khas kelapa, tidak tengik dengan nilai 4,30, rasa khas minyak kelapa 4,00, dan warna jernih 4,10.